Measurement reliability of endotracheal tubes cuff pressure between industrial and handmade devices - Cunha, Ennie Luana Melo; Sales, Roberta Duarte; Araújo, Zênia Trindade Souto; Gomes, Girlene Camilo; Mendes, Ciro Leite; Santos, Heleodório Honorato dos; Maciel, Simone dos Santos (Manual Therapy, Posturology & Rehabilitation Journal, 2017)
Introduction: The cuff pressure is measured in industrial equipment, however, be valid in the craft equipment is still questioned. Objective: To evaluate the reliability of the measurement methods of cuff pressure endotracheal tubes with industrialized and handmade equipment. Method: Were analyzed 40 endotracheal tubes, two brands (Solidor and Ruschelit) and different diameter (8,0 mm and 8,5mm), inflated 20mL of air in the pilot balloon with plastic syringe and 20 mL, followed by pressure measurement device with industrial (cmH2 O) and handmade device (mmHg). After the conversion of cmH2O values for mmHg, the reliability and agreement of measurements were performed by intra-class correlation (ICC) and Bland-Altman tests, respectively, using SPSS (version 15.0) and adopting a significance level of 5% for all comparisons. Results: The data showed similarity between the different pressure equipment, brands and diameter, and demonstrated strong correlation and agreement between the methods. Tube Rus8,0mm industrial versus handmade (28.2±5.8 vs 28.4±6.2 mmHg: ICC=0.998; bias=0.20); Tube Solidor8.0mm industrial versus handmade (75.9±1.1 vs 76.4±1.2 mmHg: ICC=0.878; bias=0.40); Tube Rus8.5mm industrial versus handmade (17.1±8.8 vs 17.8±8.9 mmHg: ICC=0.999; bias=0.67); Tube Sol8.5mm industrial versus handmade (78.7±4.7 vs 78.6±4.6 mmHg: ICC=0.996; bias=-0.1). Conclusion: The high reliability and agreement presented in this study suggest that the cuff pressure gauge handmade can be used safely to evaluate the cuff pressure of the endotracheal tube.